DEVELOPMENT OF A COST MANAGEMENT FRAMEWORK FOR POLYTECHNIC STUDENT INNOVATION PROJECTS: A FUZZY DELPHI ANALYSIS - Abd Rashid, Mohd Norulhisham; Shafie, Nurull Zuraida (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Inefficient cost management is often a major constraint in ensuring that student innovation projects in Technical and Vocational Education and Training (TVET) institutions successfully transition from the prototyping phase to commercialization. This study aims to develop and validate a systematic cost management framework for student innovation projects using the Fuzzy Delphi Method (FDM). Ten experts from the Mechanical Engineering and Commerce Departments were selected as the evaluation panel to reach a consensus on the framework’s elements. The research instrument consisted of 20 items covering five key dimensions: 1. Planning and Cost Estimation, 2. Development Cost Management, 3. Commercialization Strategy, 4. Control and Sustainability, and 5. Impact Assessment. The findings revealed that 17 out of 20 items achieved expert consensus with a threshold value (d) ≤ 0.2, a consensus percentage exceeding 75%, and a defuzzification value > 0.5. The “Raw Material Cost Estimation” item ranked the highest, while elements such as “Opportunity Cost” were discarded due to perceived lack of practicality. The final framework provides a structured guideline to enhance financial accountability and project management literacy among students. Consequently, this framework has the potential to be adopted as a standard reference module for final-year project courses in Polytechnics to support the sustainability of TVET innovation.